AB1139 Centre Characteristics Determine Ambulatory Care and Referrals in Patients with Spondyloarthritis. (9th June 2015) - Andrés, M.; Sivera, F.; Pérez-Vicente, S.; Vela, P.; Carmona, L.
Abstract : Objectives: To describe the variability in rheumatology visits and referrals to other medical specialties of patients with spondyloarthritis (SpA), and to explore factors that may influence such variability. Methods: Nation-wide cross-sectional study performed in 2009-2010. Randomly selected records of patients with a diagnosis of SpA and at least one visit to a rheumatology unit within the previous two years were audited. The rates of rheumatology visits and of referrals to other medical specialties were estimated – total and between centres – in the study period. Multilevel regression was used to analyse factors associated to variability, and to adjust for clinical and patient characteristics. Results: 1, 168 patients' records (45 centres) were reviewed, mainly ankylosing spondylitis (55.2%) and psoriatic arthritis (22.2%). The patients had incurred in 5, 908 visits to rheumatology clinics (rate 254 per 100 patient-years), 4, 307 visits to other medical specialties (19.6% were referrals from rheumatology), and 775 visits to specialised nurse clinics. An adjusted variability in frequenting rheumatology clinics of 15.7% between centres was observed [Table ]. This was partially explained by the number of faculties (β 0.309; 95%CI 0.155, 0.463) and trainees (β -1.441; 95%CI -2.526, -0.356). The adjusted intercentre variability for referrals to other specialties was 12.3%, and it was associated with urban settings (OR 1.237; 95%CI 1.309, 1.399), number of procedures (OR 1.011; 95%CI 1.001, 1.020), and existence of SpA dedicated clinics (OR 1.762; 95%CI 1.101, 2.821); the probability of a patient with SpA of being referred to other specialist may increase up to 25% depending on the treating centre. Conclusions: Frequenting rheumatology clinics and referrals to other specialists significantly varies between centres, after adjustment by patient characteristics. Disclosure of Interest: None declared